Physiology of Immune System: Regulation of Stem Cell Survival - Arra, Claudio; Turco, Maria C.; D'avenia, Morena; Torino, Gaetano; Giudice, Aldo; Pascale, Maria (Recent Patents on Endocrine, Metabolic & Immune Drug Discovery (Discontinued), 2009)
The immune system is a complex defense mechanism, able to protect the body against pathogens. It consists of a network of cells, tissues, and organs that work together to protect the body. Leukocytes are key operatives of the immune system. Cells destined to become immune cells, like all blood cells, arise in your body's bone marrow from stem cells (HSC). A large body of evidence show the transcription factors play critical roles in the homeostasis of T cells, B cells, neutrophils and other non-lymphoid leneages. This review discusses the role of the Smek (Suppressor of mek null) gene, that acts in the stress response pathway of animals by binding to and enhancing the transcription of FoxO transcription factors. Furthermore, the review deals with tachykinins, involved in neurotransmission and immune/hematopoietic modulation. Both molecules, objects of recent patents, may have real therapeutic potential.
Keywords: Immune system